Effect of Chicken Manure Fertilizer on Growth of grafting Seedlings of the Conjoined Orange (Citrus Nobilis Sin) Plant and Pomelo (Citrus Grandis L. Osbeck) - I Wayan Riandana; Ida Bagus Komang Mahardika; Gusti Bagus Udayana (SEAS (Sustainable Environment Agricultural Science), 2019)
This research aims to determine the distribution of chicken manure dosage treatments to the growth of grafting seedlings of varieties of Siamese and Grapefruit. This research is a field experiment conducted in Belancan Village, Kintamani District, Bangli Regency from April to December 2017. This study used a Randomized Block Design (RBD) with 2 factors arranged factorial. Thus in 10 combinations were repeated three times so that in 30 polybags the treatment combination. The interaction between the treatments of chicken manure with citrus varieties (A Ã— J) significantly affected the shoot wet weight variable and the open dry weight variable. The highest wet weight value obtained in the treatment of chicken manure doses of 62.5 grams per polybag (A4) is 57.83 (g) increased 629% when compared to the lowest yield in the treatment of chicken manure 0 grams per polybag (A0) which is only 7.93 (g). In the treatment of shoots wet weight orange varieties obtained the highest value in the treatment of pomelo (JB) In the treatment of chicken manure 65.5 grams per polybag that is 57.83 (g) increased 188.71% when compared with the lowest results of the dosage treatment of chicken manure fertilizer 0 gram per polybag that is 20.03 (g).